Corruptors Remission Controversy: A Review of Human Rights and Justice Perspective - Aji Mulyana; Salsa Octaviani Suryanto; Kayla Andini Putri; Ajeng Permana; Salsabila Hadi Salsabila Hadi Aulia (Jurnal Wawasan Yuridika, 2024)
The granting of remission to prisoners convicted of corruption in Indonesia has sparked controversy in the context of human rights and justice. The purpose of this study is to analyze remission policies in Indonesia for prisoners convicted of corruption. The methods used are normative juridical and qualitative analysis, which review relevant legislation and court decisions. The results of the study show that the revocation of Government Regulation No. 99 of 2012 opens up opportunities for convicted corruption offenders to obtain disproportionate remissions, thereby reducing public awareness and trust in the penal system. The diverse characteristics of corruption perpetrators—in terms of position, modus operandi, state losses, and socio-economic background—are somewhat inconsistent with the rehabilitative approach in the correctional system. Therefore, a more selective, fair, and corruption-eradicating remission policy is needed so that this study contributes to the development of correctional law and sentencing policy.